Farelo de trigo como matéria-prima para produção de papel - Dassoler, Karine (2017)
Paper is an extremely versatile material that, by possessing chemical, physical and mechanical unique properties, can have several applications such as writing and printing, newspaper production, sanitary papers, packaging, among others. Wood is the main raw material used in the paper industry and only 40 and 50% of its total initial mass is applied in paper production. The most explored wood fiber in this sector is eucalyptus and Brazil has the largest surface area planted with trees. This monoculture has caused several environmental impacts, such as extreme dependence on agrochemicals and high consumption of water, typical of the species, which are worsened since eucalyptus is not a native Brazilian tree. It is extremely important the development of technologies that search for sustainable solutions and reduce these environmental impacts. Several studies have been carried out using alternative raw materials for paper manufacture. The results have shown that is possible to replace wood without major changes in the process and equipment already used. Wheat has significant importance in the global agricultural economy, since it is the second most-produced cereal. The wheat husk or bran is the grain part that is not used for milling flour production. It is a byproduct of the milling industries rich in cellulose and hemicellulose. Thus, this study aimed at using wheat bran as raw material for paper production by soda process. Three tests were performed, the first using a H-Factor of 800 and an alkali concentration of 14%, the second and the third using 15 minutes of time with alkali concentrations of 12% and 16%, respectively. The best operating condition was with an alkali concentration of 12% and cooking time of 15 minutes. In this condition, pulp yield was 35.08% and it was possible to produce paper in a proportion of up to 50% ratio of wheat bran pulp combined with eucalyptus pulp. It was possible to maintain the physical-mechanical properties in the paper produced, which is an alternative that causes less environmental impact during the production process and avail an agroindustrial residue.